2019
DOI: 10.1016/j.ijcha.2019.100373
|View full text |Cite
|
Sign up to set email alerts
|

Schistosomiasis-associated pulmonary arterial hypertension: survival in endemic area in Brazil

Abstract: HighlightsThe PHC registry equation accurately predicted survival in Sch-PAH patients.Sch-PAH survival cannot be safely predicted using only validated clinical variables only.Survival studies in endemic regions of Schistosomiasis are needed to establish the real prognosis of Sch-PAH in the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
4
0
2
Order By: Relevance
“…Clinical studies in SchPAH are scarce and restricted to a few PH centers in the world, largely in Brazil (67)(68)(69)(70)(71)(72)(73)(74)(75)(76). Additionally, most of the clinical data reported to date were generated in centers situated in non-endemic areas for schistosomiasis (62,64,65,(67)(68)(69).The classic comparator disease for SchPAH is IPAH, which occurs worldwide and has been much more widely studied despite a much lower disease burden (the incidence is approximately 1 case/million individuals/year) (77).…”
Section: Differences In Presentation and Prognosis Of Schpah Comparedmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies in SchPAH are scarce and restricted to a few PH centers in the world, largely in Brazil (67)(68)(69)(70)(71)(72)(73)(74)(75)(76). Additionally, most of the clinical data reported to date were generated in centers situated in non-endemic areas for schistosomiasis (62,64,65,(67)(68)(69).The classic comparator disease for SchPAH is IPAH, which occurs worldwide and has been much more widely studied despite a much lower disease burden (the incidence is approximately 1 case/million individuals/year) (77).…”
Section: Differences In Presentation and Prognosis Of Schpah Comparedmentioning
confidence: 99%
“…The SchPAH mortality rate has been reported at 9.7 deaths per 1000 patients/month in endemic areas ( 75 ). The clinical course of SchPAH is believed to be more benign compared to IPAH or PAH associated with connective tissue diseases ( 73 ), even in the absence of specific PAH treatment ( 69 ).…”
Section: Differences In Presentation and Prognosis Of Schpah Comparedmentioning
confidence: 99%
“…The clinical course of SchPAH may be more benign than IPAH or PH associated with connective tissue diseases, 25 even in the absence of specific PAH treatment. 26 Treatment-naïve SchPAH patients have been reported to have overall survival rates at 1, 2, and 3 years of 95%, 95%, and 86%, respectively, 26 although a more recent series from an endemic setting reported 1-, 3-, and 5-year survival estimates of 92%, 75%, and 51%, respectively, 27 figures closer to the prognosis in IPAH. A recent systematic review that included 18 studies concluded that SchPAH has a better prognosis than IPAH, 28 despite presenting with initially similar hemodynamics, although it should be cautioned that many of these patients were studied in nonendemic settings.…”
Section: Prognosis and Response To Therapymentioning
confidence: 99%
“…De acordo com o presente estudo, contudo, tal diferença não pode ser explicada por peculiaridades no comportamento dinâmico ao esforço, ou por alterações no balanço autonômico avaliado pela microneurografia e pela variabilidade de frequência cardíaca. A caracterização hemodinâmica dos pacientes foi igualmente semelhante a descrições prévias, dentro ou fora de locais onde a esquistossomose é endêmica 8,68 .…”
Section: Discussionunclassified
“…Embora tal achado possa ser decorrente de evolução adaptativa de longa data, à semelhança de pacientes com cardiopatia congênita, é preciso lembrar que mecanismos inflamatórios decorrentes da infecção pelo Schistosoma mansoni são importantes da gênese da HAP-Sch 17,22,23 . Também sugerindo um curso prolongado de doença, encontra-se o dado de que esses pacientes se apresentam mais velhos ao diagnóstico quando comparados aos pacientes com HAPI, como encontrado em nosso estudo e já relatado anteriormente 8,68 . Por outro lado, é possível que as alterações endoteliais nesse grupo de pacientes sejam decorrentes de diferentes mecanismos inflamatórios, ou que particularidades fisiológicas determinem evoluções clínicas distintas.…”
Section: Discussionunclassified